2019
DOI: 10.1016/j.bjorl.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Steroid vs. antibiotic impregnated absorbable nasal packing for wound healing after endoscopic sinus surgery: a randomized, double blind, placebo-controlled study

Abstract: The results of this study reveal the significant positive influence of steroid- and antibiotic-impregnated biodegradable nasal packing on the postoperative healing process and patient satisfaction compared to the saline soaked dressing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(45 citation statements)
references
References 20 publications
0
44
0
1
Order By: Relevance
“…Nasopore ® is a bioabsorbable nasal packing that is made of a fragmentable poly (DL-lactide-co-E-caprolactone) urethane. In a randomized, placebo-controlled study, Grzeskowiak and colleagues compared the efficacy of the Nasopore ® packing impregnated with either steroid (betamethasone) or antibiotics (ciprofloxacin) [51]; Nasopore ® impregnated with saline was used as a placebo. The study indicated a significant improvement with both steroid-eluting and antibiotic-eluting bioabsorbable packing on the postoperative healing process and patient satisfaction as compared to saline-soaked packing.…”
Section: Nasal Packingmentioning
confidence: 99%
See 1 more Smart Citation
“…Nasopore ® is a bioabsorbable nasal packing that is made of a fragmentable poly (DL-lactide-co-E-caprolactone) urethane. In a randomized, placebo-controlled study, Grzeskowiak and colleagues compared the efficacy of the Nasopore ® packing impregnated with either steroid (betamethasone) or antibiotics (ciprofloxacin) [51]; Nasopore ® impregnated with saline was used as a placebo. The study indicated a significant improvement with both steroid-eluting and antibiotic-eluting bioabsorbable packing on the postoperative healing process and patient satisfaction as compared to saline-soaked packing.…”
Section: Nasal Packingmentioning
confidence: 99%
“…Nasal Pack Drug Delivered Outcomes [49] Silsos gel Silver Improves SNOT22 score and mucosal healing [50] SinuBandFP Fluticasone propionate Improves polyp score, adhesion, pain [51] Nasopore Betamethasone Improves healing and satisfaction Ciprofloxacin Improves healing and satisfaction…”
Section: Studymentioning
confidence: 99%
“…But when expanded to time periods greater than 90 days, significant differences are not observed between groups. 43 Due to the chronic nature of CRS, consistent, long-term results are necessary to achieve appropriate improvement. Additionally, the nasal packing material has yet to show significant promise as a potential therapeutic intervention due to the lack of reliability in drug release.…”
Section: Potential Nonstent Topical Therapiesmentioning
confidence: 99%
“…Recent studies have shown some success in short‐term use of nasal packing materials with antibiotic groups demonstrating improved endoscopic scoring compared to control. But when expanded to time periods greater than 90 days, significant differences are not observed between groups 43 . Due to the chronic nature of CRS, consistent, long‐term results are necessary to achieve appropriate improvement.…”
Section: Potential Nonstent Topical Therapiesmentioning
confidence: 99%
“…There were then 3 prospective, randomized, double-blinded, controlled trials, [18][19][20] which have all shown that POSE and/or LK scores were significantly improved at various time points during the postoperative period (Table 1). These trials differed in terms of the length of NasoPore used, choice of corticosteroid, and method of study control (intrapatient vs interpatient).…”
Section: Evidence On Clinical Outcomesmentioning
confidence: 99%